Effect of uric acid in animal models of ischemic stroke: A systematic review and meta-analysis. Issue 4 (April 2021) - Aliena-Valero, Alicia; Baixauli-Martín, Júlia; Castelló-Ruiz, María; Torregrosa, Germán; Hervás, David; Salom, Juan B
Addition of uric acid (UA) to thrombolytic therapy, although safe, showed limited efficacy in improving patients' stroke outcome, despite alleged neuroprotective effects of UA in preclinical research. This systematic review assessed the effects of UA on brain structural and functional outcomes in animal models of ischemic stroke. We searched Medline, Embase and Web of Science to identify 16 and 14 eligible rodent studies for qualitative and quantitative synthesis, respectively. Range of evidence met 10 of a possible 13 STAIR criteria. Median (Q1, Q3) quality score was 7.5 (6, 10) on the CAMARADES 15-item checklist. For each outcome, we used standardised mean difference (SMD) as effect size and random-effects modelling. Meta-analysis showed that UA significantly reduced infarct size (SMD: −1.18; 95% CI [−1.47, −0.88]; p  < 0.001), blood-brain barrier (BBB) impairment/oedema (SMD: −0.72; 95% CI [−0.97, −0.48]; p  < 0.001) and neurofunctional deficit (SMD: −0.98; 95% CI [−1.32, −0.63]; p  < 0.001). Overall, there was low to moderate between-study heterogeneity and sizeable publication bias. In conclusion, published rodent data suggest that UA improves outcome following ischemic stroke by reducing infarct size, improving BBB integrity and ameliorating neurofunctional condition. Specific recommendations are given for further high-quality preclinical research required to better inform clinical research.